The role of xerogel in immobilising carbon quantum dots derived from oil palm mesocarp fibre: a potential adsorbent for CO2 capture / Aimi Solihah Zaul Kapri and Norhusna Mohamad Nor - Zaul Kapri, Aimi Solihah; Mohamad Nor, Norhusna (Universiti Teknologi MARA Cawangan Pulau Pinang, 2025)
Carbon quantum dots (CQDs) often suffer from agglomeration and structural instability, significantly reducing their adsorption efficiency and reusability. This study investigates the role of xerogel in stabilising and immobilising CQDs derived from oil palm mesocarp fibre (MF) as a potential CO2 absorbent. The extracted MF cellulose was synthesised into CQDs via hydrothermal treatment and subsequently immobilised within a xerogel matrix (X-MF-CQDs). The CO2 adsorption performance was evaluated through breakthrough and sorption capacity experiments, where X-MF-CQDs at a 1:50 dilution exhibited the highest sorption capacity (129.04 mg/g) and a moderate breakthrough time (61.3 s). BET analysis confirmed a low surface area (1.7011 m2/g), while pore size distribution revealed dominant micro porosity ( ̴ 20 A), crucial for CO2 capture. FTIR analysis indicated the presence of N-H, C=N, C-O, and C-S bonds, confirming successful heteroatom doping. CHNS analysis revealed a composition of 50.33 % C, 22.78 % O, and 0.6 % S, highlighting the contribution of heteroatoms in CO2 affinity. HRTEM and FESEM analyses confirmed uniform CQDs dispersion within the xerogel matric, effectively minimising agglomeration and enhancing adsorption. These findings demonstrate the effectiveness of xerogel-immobilised CQDs (X-MF-CQDs) as a stable and efficient CO2 adsorbent, promoting sustainable waste valorisation strategies.